Study of Anti-inflammatory Activity of a New Non-opioid Analgesic on the Basis of a Selective Inhibitor of TRPA1 Ion Channels - Beskhmelnitsyna, Evgeniya A.; Pokrovskii, Mikhail V.; Kulikov, Aleksandr L.; Peresypkina, Anna A.; Varavin, Evgeniy I. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2019)
Introduction: Nowadays, the group of NSAIDs is used the most widely in order to treat the inflammatory process. But its long-term administration increases the risk of complications of pharmacotherapy. Therefore, today it is urgent to search for new molecules that can selectively block biological targets that directly perceive inflammatory mediators. One of such targets is TRPA1. ZC02-0012, a compound from the group of substituted pyrazinopyrimidinones, which is a selective inhibitor of TRPA1 ion channel. Objective: The aim of our study was to study the anti-inflammatory activity of an innovative molecule under the laboratory code ZC02-0012 from the group of selective inhibitors of TRPA1 ion channel. Materials and Methods: Anti-inflammatory activity of ZC02-0012 was studied on the model of acute exudative inflammation of the paw in response to subplantar injection in the right hind paw of mice with 0.02 ml of 2% formaldehyde solution. The mass of the paw was measured after 4 hours (peak edema) after phlogistic injection. The test substance and the reference drug was administered intragastrically or intramuscularly 45 minutes before the injection of formaldehyde solution. The presence and intensity of antiinflammatory activity was judged by the inhibitory effect, represented in percent. Results and Discussion: Selective inhibitor of the TRPA1 ion channel ZC02-0012 revealed the anti-inflammatory activity at doses of 3 and 9 mg/kg, its intensity is comparable to diclofenac sodium. Conclusion: The selective inhibitor of the ion channel TRPA1, a substance under code ZC02-0012, has an anti-inflammatory activity comparable with diclofenac sodium.
Keywords: TRPA1 ion channel